2021
DOI: 10.1016/j.ijepes.2021.106978
|View full text |Cite
|
Sign up to set email alerts
|

Controllable transmission networks under demand uncertainty with modular FACTS

Abstract: The transmission system operators (TSOs) are responsible to provide secure and efficient access to the transmission system for all stakeholders. This task is gradually getting challenging due to the demand growth, demand uncertainty, rapid changes in generation mix, and market policies. Traditionally, the TSOs try to maximize the technical performance of the transmission network via building new overhead lines or physical hardening. However, obtaining public acceptance for building new lines is not an easy ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…For example, the study by Sanjari and Karami (2020) has suggested using integrated battery storage to regulate the energy resource scheduling under uncertain deviation of loads. The uncertainty of demand not only affects the distribution sectors but also has a potential impact on developing the transmission lines as explained by Soroudi (2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, the study by Sanjari and Karami (2020) has suggested using integrated battery storage to regulate the energy resource scheduling under uncertain deviation of loads. The uncertainty of demand not only affects the distribution sectors but also has a potential impact on developing the transmission lines as explained by Soroudi (2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…e economic model of DR is defined in (13). is model is used to evaluate the impact of consumer participation in DR on the load profile.…”
Section: Objective Functionsmentioning
confidence: 99%
“…These problems can affect the system's stability and may lead to failure. To overcome these disturbances and ameliorate the power quality [9], flexible alternating current transmission system (FACTS) ISSN: 2088-8694  devices are often used [10], [11]. The FACTS can be introduced in the power system network to increase the power transfer capability of the transmission line and to ameliorate the voltage stability [12], [13].…”
Section: Introductionmentioning
confidence: 99%